The effects of oil price on the price of selected intermediate food products in Malaysia
A fluctuation in the oil price has been addressed by numerous previous studies as it can have great impacts on economies. An increase in oil price can result in a higher price of other goods. Sugar, egg and coconut milk are the intermediate food products that can be inevitably affected due to a higher oil price. Therefore, this present study aims to investigate the effects of oil price on the price of selected intermediate food products in Malaysia. This research narrows the focus of the investigation, to concentrate on the three types of oil price: RON95, RON97 and diesel. These oil price can major contribute to the price of selected intermediate food products (sugar, egg and coconut milk) in Malaysia. The sample period covers 84 months from 2008 to 2015. The relationship between oil price and the price of selected intermediate food products is examined by using the linear autoregressive distributed lag (ARDL) bound test. The bound test was conducted and the results show that all the variables in functional form framework are bound together in the long-run. It was also ascertained that in the long-run, the price of RON97 influences the prices of selected intermediate food products (sugar, egg and coconut milk) in Malaysia. Nevertheless, the price of diesel affects only the price of sugar, whereas RON95 is negatively and significantly associated with the price of sugar alone. The error-correction terms test results reveal that the price of diesel is positively correlated with the price of sugar respectively in the short-run. On the other hand, the findings found that the prices of RON97 significantly influenced the prices of egg and coconut milk in Malaysia. However, the prices of sugar and coconut milk had adjusted at a higher speed compared with the price of egg which had adjusted at a lower speed. Therefore, these findings are important for the government to control the price of oil in order to achieve the stability of the price of selected intermediate food products in Malaysia such as sugar, egg and coconut milk.